DAMPAK TINGKAT PERPUTARAN PIUTANG USAHA PADA PROFITABILITAS PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Evelyn, Clarissa; Marsudi, Almatius Setya (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2021)
This study tries to analyze the effect of accounts receivable turnover on company profitability. Profitability in this study is measured by the ratio of Return on Assets. This study also uses a moderating variable, namely the audit committee. This study uses a sample of 30 manufacturing companies on the Indonesia Stock Exchange in the 2016-2018 period. The analysis used is panel data regression analysis with random models and multiple linear regression. This study uses data processing software in the form of Eviews. The result of this study is that turnover has a positive and significant effect on the company's profitability.